Production and characterization of rhamnolipid biosurfactant from thermophilic Geobacillus stearothermophilus bacterium isolated from Uhud mountain - Albasri, Hibah M.; Almohammadi, Asmaa A.; Alhhazmi, Areej; Bukhari, Duaa A.; Waznah, Moayad S.; Mawad, Asmaa M. M. (Frontiers in Microbiology, 2024)
Introduction Biosurfactants have been given considerable attention as they are potential candidates for several biotechnological applications. Materials and methods In this study, a promising thermophilic biosurfactant-producing HA-2 was isolated from the volcanic and arid region of Uhud mountain, Madinah, Saudi Arabia. It was identified using 16S rRNA gene sequence analysis. The biosurfactant production ability was screened using different methods such as the drop collapse test, oil spreading test, hemolytic activity test, CTAB test, and emulsification index. The ability of rhamnolipid production by the tested strain was confirmed by the polymerase chain reaction (PCR) of rhlAB. The affinity of thermophilic HA-2 to hydrophobic substrates was also investigated. Optimization of biosurfactant production was conducted. The biological activities of produced surfactant were investigated. Results and discussion The isolated HA-1 was identified as Geobacillus stearothermophilus strain OR911984. It could utilize waste sunflower frying oil (WSFF) oil as a low-cost carbon source. It showed high emulsification activity (52 ± 0.0%) and positive results toward other biosurfactant screening tests. The strain showed high cell adhesion to hexane with 41.2% cell surface hydrophobicity. Fourier-transform infrared (FTIR) spectra indicated the presence of hydrophobic chains that comprise lipids, sugars, and hydrophilic glycolipid components. The optimization results showed the optimal factors included potato peel as a carbon source with 68.8% emulsification activity, yeast extract as a nitrogen source with 60% emulsification activity, a pH of 9 (56.6%), and a temperature of 50° (72%). The kinetics showed that optimum biosurfactant production (572.4 mg/L) was recorded at 5 days of incubation. The produced rhamnolipid biosurfactant showed high antimicrobial activity against some human and plant pathogenic bacterial and fungal isolates and high antioxidant activity (90.4%). In addition, it enhanced wheat (Triticum aestivum) growth, with the greatest enhancement obtained with the 5% concentration. Therefore, thermophilic G. stearothermophilus is a promising rhamnolipid biosurfactant producer that utilizes many organic wastes. The produced biosurfactant could be applied as a promising emulsifier, antimicrobial, antioxidant, and plant growth promoter.